Magneto-ionic suppression of magnetic vortices. Issue 1 (31st December 2021) - Chen, Yu; Nicolenco, Aliona; Molet, Pau; Mihi, Agustin; Pellicer, Eva; Sort, Jordi
ABSTRACT: Magneto-ionics refers to the non-volatile control of the magnetic properties of materials by voltage-driven ion migration. This phenomenon constitutes one of the most important magnetoelectric mechanisms and, so far, it has been employed to modify the magnetic easy axis of thin films, their coercivity or their net magnetization. Herein, a novel magneto-ionic effect is demonstrated: the transition from vortex to coherent rotation states, caused by voltage-induced ion motion, in arrays of patterned nanopillars. Electrolyte-gated Co/GdO x bilayered nanopillars are chosen as a model system. Electron microscopy observations reveal that, upon voltage application, oxygen ions diffuse from GdO x to Co, resulting in the development of paramagnetic oxide phases (CoO x ) along sporadic diffusion channels. This breaks up the initial magnetization configuration of the ferromagnetic pillars (i.e. vortex states) and leads to the formation of small ferromagnetic nanoclusters, embedded in the CoO x matrix, which behave as single-domain nanoparticles. As a result, a decrease in the net magnetic moment is observed, together with a drastic change in the shape of the hysteresis loop. Micromagnetic simulations are used to interpret these findings. These results pave the way towards a new potential application of magnetoelectricity: the magneto-ionic control of magnetic vortex states. GRAPHICAL ABSTRACT: uf0001